Effects of Macroeconomic Factors in the Performance of Micro Finance Institutions in Ecuador - Caro, Eric Joel (International Journal of Economics and Financial Issues, 2017)
Microfinance institutions give credit to people who do not have facilities of access to the financial system with the aim of using it to create or expand a business. However, these institutions may be affected, exogenously, by the situation of the country where they operate, influencing the full development of their activities, such as granting benefits to their applicants. The author analyzes the effect that macroeconomic factors may have on the performance of microfinance institutions. Ecuador is taken as the reference country, using the Savings and Credit Cooperatives Organizations (SACCO), Non-Governmental organizations and Banks, which are part of this microfinance sector. A fixed effect panel data regression was used, with a multiple imputation treatment for missing values because of the quality of the information obtained. It was found that there is no statistically significant influence on the macroeconomic variables used in the study on the performance of microfinance in Ecuador. Keywords: micro finance, Ecuador, finance, bank. JEL Classifications: G21, G23, G28